Seramik purba yang diperdagangkan di Semenanjung Malaysia - Asyaari Muhamad, (Universiti Kebangsaan Malaysia, 2010)
This article discusses about the ancient trade ceramics traded in the Malay Peninsula since the early century of the Christian era. The main focus of the study is to trace the evolution and the distribution of the foreign ancient ceramic which were traded in the important archaeological sites in Peninsular Malaysia such as at Bujang Valley, Kedah, Pulau Pinang, Melaka, Negeri Sembilan, Johor and in the East Coast states in the Peninsula. The evidence of presence of the ancient ceramics from China suggest that they were the earliest ancient trade ceramic ever found in Peninsula Malaysia. However, evidence from other ancient trade ceramics from Southeast Asia suggests that they were from Cambodia, Myanmar and Vietnam. They were found in some archaeological sites in Peninsula Malaysia. The most ancient trade ceramic pieces from Middle-East (Persian Ceramic) were also found in Bujang Valley shows that the early stage on trade between Persian and Peninsula Malaysia started since 9th Century. The most ancient pieces of ceramic belong to the Tang Dynasty (618-906). They were found in Bujang Valley indicating that the ancient trade between Malay Peninsula and China existed since the early century of Christian era. This statement not only supported by the finding of the ancient Tang ceramic but also the evidence from the Chinese written sources. The rarity of ancient trade ceramics were found in various archaeological sites in Peninsula Malaysia shows that the early stage of trading contacts between China, Middle-East and Southeast Asia with Peninsula Malaysia started very early. The factors why Peninsular Malaysia was able to sustain the early stage of trade relationship with those countries are the factors of stability of politics, economy and also its geographic setting